(3QSGdI aj EbGeI GdHQgGf Ydi GdOGFQ ef Gdadc aj bhS GdfgGQ hEQJaGY fUa GdfgGQ hEQJaGY GdhbJs - (3CHh GdhaG eMeO Hf eMeO, GdHhRLGfjs
(3ChdgG (B:s
(3dhdG eG GfJ Ydjg GjgG GdaGVd ef TQja GNdGbc hbO JLGQjfG ai gPg GdGjGe eYGdi ef GdgHg aSeYJc JMci Yf bhe ef GaGVd hbJfG Gf GdOGFQ ef Gdadc djS HYde s
(3BNQgG (B:s
(3EPG cGfJ GdTeS eG jdg Yf eYOd GdfgGQ hjchf GdOGjQ Cbd ef fUa aVd GdfgGQ hbaJ Ydjg HSghdg Gf TGA Gddg JYGdi JeJ QSGdI GHh GdhaG s
(3HYK HgG Edi CHj Ydi CMeO Hf Ydi Hf GdScQs
(3JTJed Ydi QSheGJ gfOSjIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs